Retired matches among male professional tennis players - Breznik, K.; Batagelj, V. (Journal of Sports Science & Medicine, 2012)
The aim of this study was to explore the effect of characteristics of various games and players on the proportion of retired tennis matches in the Open Era of tennis. The data included over 420,000 matches played among 17,553 tennis players in the period from 1968 to the end of 2010. The influence of the surface type was clearly confirmed, with the proportion of retired matches being higher on hard and clay courts compared to grass and carpet surfaces. Similarly, more retired matches were observed in outdoor venues than in indoor ones. The impact of other variables, tournament types, rounds at which the game was played and both players` ranks, is more ambiguous. Our interpretation of the obtained results is presented in the paper. Network analytic methods were applied to extract players with the most retired matches in their careers. Eventually, we defined a group of top tennis players and gave a more precise insight into retired matches in that group. Correspondence analysis was used to visually display the two-mode network of top players and the proportion of retired matches by surface type.